Determination of fracture toughness from the small punch test using circular notched specimens. (October 2019) - Hurst, Roger; Li, Yingzhi; Turba, Krystof
Highlights: The new type of SP specimen is a circular notched disc with thickness of 1 mm, and the diameter of the circular notch is 2.5 mm with depth of 0.5 mm. A plane strain condition is built around the crack tip which makes determination of the elastic fracture toughness KIC possible. Using Rice-Merkle model an analytic solution is proposed to estimate the J -integral for the circular notched specimen, and the procedure to determine the JIC . A so-called "Local approach" simulation has been performed to determine the J-R resistant curve and the JIC by using standard small punch tests. In comparison of the J -integral predicted in this paper with the literatures data and the master curve, a good agreement is also found. Abstract: The small punch (SP) test method is an innovative technique which shows potential for residual life assessment of components in service. The main tasks of the technique are to derive standard material properties with a limited amount of material, including strength/toughness, creep and fatigue behaviour. In order to achieve the objective, many methods have been put forward since early 1980's but even in the new EN standard in preparation no common acceptable methods are available yet for fracture mechanics testing of notched SP specimens. An investigation is carried out to exploit new approaches to determine fracture toughness from small punch tests, including a new type of notched specimen and a new analytic approach. The new type of specimen is a circular notched disc with thickness of 1 mm, and the diameter of the circular notch is 2.5 mm with depth of 0.5 mm which has been proposed and tested by JRC Petten, European Commission. The advantage of the circular notched specimen is that a plane strain condition is built around the crack tip which makes determination of the elastic fracture toughness KIC possible if the condition of small scale yielding is met. In comparing the volume of the new type specimen with the standard fracture specimens, it is only 1/5000 of that of the three point bending specimen (TPB) and 1/2000 of that of the compact tension specimen (CT). In this paper, a method based on fracture energy is proposed to estimate the J -integral for the circular notched specimen, and the procedure to determine the fracture toughness JIC is also addressed. In order to verify the proposed approach, a so-called "Local approach" analytical simulation has been performed to determine the J-R resistant curve and the fracture toughness JIC by using standard small punch tests. In comparison of the J -integral predicted in this paper with the literatures data and the master curve, a good agreement is also found.